Islamic Republic of Afghanistan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper presents estimates of the fiscal revenue cost of conflict in Afghanistan, defined as the loss of government domestic revenue due to conflict. The loss of government revenue is an important component of the humanitarian costs of conflict. In Afghanistan, almost all security spending is funded by foreign grants, which will most likely be scaled back gradually in the event of peace. Hence, any fiscal peace dividend is likely to come principally from increased revenues, as reduced security spending will be mostly offset by reduced grants. Nevertheless, size and the statistical significance of the results suggest that the order of magnitude of the estimate, around USD 1 billion, is robust. By way of counterfactual, these results imply a sizeable potential fiscal dividend for Afghanistan should peace, or at least a significant reduction in violence, materialize. Several country-specific factors, including conflict and a landlocked geography, have held back an expansion in Afghanistan's trade which could increase the country's economic resilience. Improving its external connectivity is a key factor to unlocking its trade potential including leveraging its natural resources.